2013
DOI: 10.1039/c3cc41090k
|View full text |Cite
|
Sign up to set email alerts
|

A novel Ag3AsO4 visible-light-responsive photocatalyst: facile synthesis and exceptional photocatalytic performance

Abstract: A novel Ag3AsO4 photocatalyst has been prepared via a facile precipitation method. It exhibited higher activity than Ag3PO4 or AgI in degradation of rhodamine B or methyl orange. The excellent activity of Ag3AsO4 is attributed to its more separated photogenerated carriers and high absorption capacity of visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 15 publications
1
57
0
1
Order By: Relevance
“…As for some photocatalysts with wide band gap, visible light cannot be used directly, only after depositing silver nanoparticles, these photocatalysts can absorb visible light and show visible light photocatalytic activities. This is because silver nanoparticles can absorb visible light and be excited to generate electrons and holes, joining in further photocatalytic reaction [9][10][11][12] ,just like Ag/AgCl, Ag/TiO2 materials etc.. For others, the materials can absorb visible light because of their proper band gaps and show photocatalytic activity under irradiation of visible light [13][14][15][16][17] . Ye and her group have synthesized Ag3PO4 through a co-precipitation method and their experiment showed that Ag3PO4 was a very good photooxidation catalyst in photodegradation of organic pollutants.…”
Section: Introductionmentioning
confidence: 97%
“…As for some photocatalysts with wide band gap, visible light cannot be used directly, only after depositing silver nanoparticles, these photocatalysts can absorb visible light and show visible light photocatalytic activities. This is because silver nanoparticles can absorb visible light and be excited to generate electrons and holes, joining in further photocatalytic reaction [9][10][11][12] ,just like Ag/AgCl, Ag/TiO2 materials etc.. For others, the materials can absorb visible light because of their proper band gaps and show photocatalytic activity under irradiation of visible light [13][14][15][16][17] . Ye and her group have synthesized Ag3PO4 through a co-precipitation method and their experiment showed that Ag3PO4 was a very good photooxidation catalyst in photodegradation of organic pollutants.…”
Section: Introductionmentioning
confidence: 97%
“…For example, photocorrosion is easy to occur in the mostly used CdS semiconductor because its photogenerated holes are strong enough to oxide the surface S 2À ions [12][13][14]. Silver-containing semiconductor photocatalysts like Ag 3 AsO 4 [15], AgIO 4 [16], Ag 3 PO 4 [17,18], Ag 2 CO 3 [19][20][21][22], Ag 2 CrO 4 [23,24], although highly active, are silver-containing and thus high-cost. Also, the silvercontaining semiconductors are unstable because it is energetically possible for their surface ions to undergo photocorrosion reduction or oxizidation through their photogenerated carriers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, it is urgent to develop new type of visible light driven photocatalysts [19][20][21][22]. Up to now, different visible light photocatalysts Page 4 of 33 A c c e p t e d M a n u s c r i p t 4 have been developed, such as gold nanoclusters (Au 25 (SR) 18 /TiO 2 ) [23], TiO 2-x N x [24], Rh(Pd, Pt)/BiOX(Cl, Br, I) [25], g-C 3 N 4 [26], supported plasmonic noble metal (e.g.…”
Section: Introductionmentioning
confidence: 99%